Investigation of the effects of Ni-based alloy DZ125 on the normal spectral emissivity during oxidation. (25th October 2016) - Zhao, Shunan; Li, Xunfeng; Zhou, Xiaoming; Cheng, Keyong; Huai, Xiulan
Highlights: Emissivity of Ni-based alloy at high temperatures is measured during oxidation. The emissivity increases as temperature increases and wavelength decreases. The oscillations of the emissivity occur due to interference effect. Fitting models are developed to study the change of the emissivity quantitatively. Abstract: The normal spectral emissivity of Ni-based alloy DZ125 during oxidation is experimentally measured at 810, 916 and 998 °C for 12 h in air over the wavelength from 1.35 to 2.35 μm. The combined standard uncertainty of the normal spectral emissivity is less than 3%. The oscillations of the emissivity and the effects of oxidation temperature, heating time and wavelength on the emissivity are investigated. The oscillations of the emissivity are formed by the interference effect of radiation between the surfaces of the substrate and the oxidation film. The interferential extremums of the emissivity shift towards larger wavelengths as the oxidation process proceeds. The results show that the normal spectral emissivity increases basically with increasing temperature and decreasing wavelength except for the occurrence of the oscillations of the emissivity. The normal spectral emissivity increases rapidly at the initial heating time, and the change of emissivity becomes slow when the oxidation is going to be saturated. Besides, the emissivity fitting models versus heating time and wavelength are established, which fit the experiment data very well. The emissivity relative errors of the fitting models are less than 3%.